Isolation and Identification of Some Bacterial Species from Otitis Media Patients in Kerbala City - Taama Khader, Laith Yahya; fahad ali, Remah nouri; Hamid Jabbar, Omal Baneen Aqeel; Gazi, Taif Allawi Jiad (American Journal of Biology and Natural Sciences, 2024)
This investigation began in last January of this year at the Applied Medical Sciences College’s Department of Clinical Laboratories. The study’s aims were to identify and diagnose the most frequent bacterial pathogens responsible for otitis media, as well as to explore the antibiotic sensitivity of bacterial isolates and the role of different factors on illness spread. (30) samples of purulent material in the middle ear were obtained in the form of ear swabs from patients diagnosed with otitis media by otolaryngologists within private clinics. It was for different age groups, ranging from 18 to 62 years, for both sexes. The age distribution of otitis media patients showes age groups (21-30 years) and (41-50 years) had the highest percentage incidence (both categories were 26.9%). In the Public Health Laboratory of Karbala City, the samples were grown on various culture medium and diagnosed in the laboratory based on cultural characteristics, Gram stain findings, and a variety of biochemical tests such as Oxidase, Coagulase, Catalase, and others. The results of the bacterial isolation showed a predominance of Pseudomonas aeroginosae bacteria by 34.61%, followed by Proteus mirabilis bacteria by 26.92%, Staphylococcus aureus by 19.23%, and Escherichia. coli by 11.53%. In addition, Serratia marcescens and Providencia were isolated by 3.84%each separately. While no growth occurred in the remaining four sample. The most effective antibiotics were, ciprofloxacin, Levofloxacin, Amikacin, meropenem, and Piperacillin- tazobactam. The least effective antibiotics were found to be tetracycline, Impicilin, Cefotaxima and Vancomycin. on the other hand, were considerably resistant to commonly used antibiotic penicillin. Among the 26 cases, the number of males with OM was 58% higher than number of women (42%). Cold or upper respiratory infection, smoking or passive smoking, seasonal allergy symptoms, other pathological variables such as gastroesophageal reflux disease, hereditary factors and bad behaviors are examples of etiology and risk factors for otitis media infection.